2022
DOI: 10.1021/acscatal.2c01873
|View full text |Cite
|
Sign up to set email alerts
|

Introducing Co–O Moiety to Co–N–C Single-Atom Catalyst for Ethylbenzene Dehydrogenation

Abstract: While single-atom catalysts (SACs) have been extensively studied as a type of high-atom-efficiency heterogeneous catalyst, their reaction stability under high temperature reductive atmosphere is yet to be addressed. In this work, we introduced a Co–O moiety to Co–N–C SACs by employing glutamic acid as both a N,O-bidentate ligand of Co­(II) and a source for N-doped carbon. After undergoing pyrolysis in N2 at 900 °C, the complex transformed into the CoN3O1–OH2 structure and subsequently to the CoN3O1 structure u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 84 publications
(114 reference statements)
2
17
0
Order By: Relevance
“…Soft X-rays are often used to probe K-edges of light elements like C (283 eV), N (402 eV), or O (532 eV). For single atom catalysts, this offers the possibility to get complementary information on the surrounding ligands that basically comes from the support. , Also, L- and M-edges of many elements are accessible only with tender X-rays, such as the L 3 -edges of Rh (3004 eV), Pd (3173 eV) or Ag (3351 eV). Such near-edge X-ray absorption fine structure (NEXAFS) spectra often yield more structural information as the excited electrons are stronger influenced by valence electrons than the energetically deeper lying K-shell electrons.…”
Section: Introductionmentioning
confidence: 99%
“…Soft X-rays are often used to probe K-edges of light elements like C (283 eV), N (402 eV), or O (532 eV). For single atom catalysts, this offers the possibility to get complementary information on the surrounding ligands that basically comes from the support. , Also, L- and M-edges of many elements are accessible only with tender X-rays, such as the L 3 -edges of Rh (3004 eV), Pd (3173 eV) or Ag (3351 eV). Such near-edge X-ray absorption fine structure (NEXAFS) spectra often yield more structural information as the excited electrons are stronger influenced by valence electrons than the energetically deeper lying K-shell electrons.…”
Section: Introductionmentioning
confidence: 99%
“…To further con rm this optimum Cu−cis−N 2 C 2 Cl−O1 con guration, we performed XANES modeling based on Finite Difference Method Near Edge Structure (FDMNES) calculation, which was usually reported to identify the metal single−atom coordination structure of M−N−C. 49 Figure 4f showed that the experimental simulation spectra presented a relatively satisfactory agreement on the basis of the Cu−cis−N 2 C 2 Cl−O1 model. Moreover, the corresponding differential charge density analysis discovered that when the epoxide group existed in the vicinal location of Cu−cis−N 2 C 2 Cl center, the charge state of single−atom Cu became more positive due to the inductive effect of oxygen atom in functional epoxide group, in agreement with the previous report 37 (Figure 4g and Figure 4h).…”
Section: Resultsmentioning
confidence: 75%
“…[ 46 ] In the Fourier‐transformed k 3‐weighted extended X‐ray absorption fine structure (EXAFS) spectra (Figure 3h), G‐CoNOC shows a relatively broad peak at a distance of 1–2 Å caused by the backscattering of light atoms of N and O, which can be ascribed to the CoN/O first coordination shell. [ 47 ] Moreover, the EXAFS fitting result confirm that the first shell of the Co atom is approximately coordinated to two N atoms and two O atoms, implying the formation of the CoN 2 O 2 bonds in G‐CoNOC (Figure 3i; Table S4, Supporting Information).…”
Section: Resultsmentioning
confidence: 89%